Decoding Vitruvius — Modulation of a Sequenced Nominal Value of a Fixed Module by Ad Triangulum Geometry - Duško Čikara (Peristil)
The sequencing of circles congruent with a (divided) column diameter – a visualization of the Vitruvian concept of a fixed module – is expanded by the inclusion, in the same scale, of geometric figures intrinsic to the ad triangulum method. The indication of continuous use of the proposed proportional system from Classical Antiquity to the 18th century points to the existence of a single canon for designing intercolumnar plane and fenestration.